2021
DOI: 10.1080/10899995.2021.1965419
|View full text |Cite|
|
Sign up to set email alerts
|

Student perceptions and performance in a traditional, flipped classroom, and online introductory soil science course

Abstract: Innovative didactive strategies such as online learning and flipped classroom can improve student performance while maximizing university resources and personnel. Assessing how students perceive courses designed using these strategies, as well as perform within them, is becoming increasingly important. An introductory soil science course at a 4-year land-grant university was taught (1) face-to-face (FTF, n = 110) with one 50-minute lecture per week and a 2-hour lab twice per week, using (2) flipped classroom (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Modern learning becomes fragmented, more focused and cheaper, not losing the quality using online platforms (Condruz Bacescu, 2018). Online Learning may maximize university resources and increase university reach and accessibility without decreasing the quality of education; focus on participants' perception (Ramirez II et al, 2021). According to previous findings on providing similar courses, several pieces of advice were introduced.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Modern learning becomes fragmented, more focused and cheaper, not losing the quality using online platforms (Condruz Bacescu, 2018). Online Learning may maximize university resources and increase university reach and accessibility without decreasing the quality of education; focus on participants' perception (Ramirez II et al, 2021). According to previous findings on providing similar courses, several pieces of advice were introduced.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This technique has been used in introductory soil science classes with results reported in the soil education literature (Long et al, 2016;Ramirez et al, 2021). Student response to the flipped soil science classroom has typically been positive (Long et al, 2016;Ramirez et al, 2021) with measures of learning performance similar to traditional classes (Ramirez et al, 2021). Jelinski et al (2019) reported that ∼4% of classroom hours in introductory soil science classes taught in the United States were delivered using flipped classroom techniques.…”
Section: Modes Of Deliverymentioning
confidence: 99%
“…Flipped classrooms have been used in recent years in an attempt to increase student engagement in a subject. This technique has been used in introductory soil science classes with results reported in the soil education literature (Long et al, 2016;Ramirez et al, 2021). Student response to the flipped soil science classroom has typically been positive (Long et al, 2016;Ramirez et al, 2021) with measures of learning performance similar to traditional classes (Ramirez et al, 2021).…”
Section: Modes Of Deliverymentioning
confidence: 99%
“…e result shows that the challenges of using educational content are the nonavailability of materials, lack of motivation of the educators, lack of skill and strategies, nancial constraints, lack of appropriate materials in the textbook, time constraints, lack of support from power, and lack of geographical learning materials. Student performance may be improved by using online learning and a split classroom, which can maximize university resources and people [2]. In the study, students who had greater starting levels of individual moral disengagement or who were in classes with higher initial levels of collective moral disengagement reported more o ine and online in the split classroom [3].…”
Section: Introductionmentioning
confidence: 99%